Pengaruh Temperatur Penyimpanan Terhadap Mutu dan Kualitas Minyak Goreng Kelapa Sawit - Fadly Husain; Ismail Marzuki (Fakultas Teknik, 2021)
The MGKS storage temperature can cause changes in the percentage of free fatty acids (FFA), peroxide number (PV) and oil color so that the quality and quality of the oil decreases. This study aims to comprehensively analyze the factors related to the quality of palm cooking oil based on storage temperature parameters. Titration method is used to determine changes in FFA and PV values, while color determination uses a lovibond tintometer to analyze changes in these parameters based on changes in storage temperature in the range of 18 0C - 36 0C, treatment increases every 2 0C. The average change in the FFA value for every 2 0C increase in the sample Sp.A = 0.1071 %; Sp.B = 0.1097 %; Sp.C = 0.1111 %. Changes in PV of Sp.A samples; Sp.B and Sp.C respectively 1.152 meq/kg; 1.266 meq/kg and 1,352 meq/kg, while the color changes that appear in the three samples are 2.34; 2.46 and 2.67. These results show that every 2 0C increase in MGKS storage temperature affects the quality and quality of the oil. MGKS Sp.A is more stable than samples Sp.B and Sp.C. Changes in the FFA value of the three samples were stable in the temperature range 18 0C - 36 0C. Changes in the FFA value of the three samples were stable in the temperature range of 18 0C - 36 0C. Sp.A samples are more stable in maintaining PV values and color against changes and increases in storage temperature compared to Sp.B and Sp.C.